DEVELOPMENT INEQUALITY OF NEW AUTONOMOUS ECONOMIC REGIONS IN LAMPUNG PROVINCE, 2005-2013 - Ambya, Ambya (AFEBI Economic and Finance Review, 2018)
Euphoria to decentralization and regional autonomy in 2000 seemingly causes the decision makers to provide more priority to allocation and transfer, such as public allocation funds and revenue sharing which provides broad discretion for regional governments to manage the use. The role of specific allocation funds which are able to be a trusted stimulus for reaching the national development target and prioritize externalization from regional public service which is ignored. The allocation of balancing funds has a strategic and primary purpose which is the encouragement of a relatively high economic growth and does not cause inequality. The source of funds of the new autonomous regions other than from locally generated revenue are also from transferred funds from the central government in the form of public allocation funds, specific allocation funds and revenue sharing. Those sources of funding contribute to the creation of regional economy development inequality. Research results show that in the last three years the inequality of economic development in new autonomous regions has narrowed. That condition is sustained by the willingness of public allocation funds, specific allocation funds, and while revenue sharing does not significantly influence economic development inequality in the regions. JEL Classification: H70, H77, O10 Keywords: Economic Growth, Inequality, Transfer funds